What are the main sources of air pollution in Sofia, Bulgaria, and how do they impact human health in the city? - Anna Shuleva (Molecular Frontiers Journal, 2023)
In our modern world, air pollution is a significantly increasing issue. Sofia, the capital city of Bulgaria, is one of the most polluted cities in Europe. It has been a long-standing issue, with pollution levels regularly exceeding the recommended limits set by the World Health Organization. The main causes of pollution in Sofia include the burning of garbage for residential heating, and emissions from vehicles due to heavy traffic. These factors especially worsen the situation during winter because of low winds and temperature inversions. This can be incredibly harmful to the health of the residents, with long-term exposure causing lung infections or cancer and possibly leading to death. In recent years, several steps have been taken by the municipality and the residents to address the issue, some of which have proven successful. However, there are still further efforts needed to be undertaken.